Design of UAV wireless power transmission system based on coupling coil structure optimization - Yixin Yan; Wan Shi; Xiaobing Zhang (EURASIP Journal on Wireless Communications and Networking, 2020)
Abstract With the development of unmanned aerial vehicle (UAV), it has been used in many fields, such as aerial photography, military, and transportation. However, it is a challenge for charging due to its short battery life. Wireless charging has been considered as a good UAV solution. In this paper, we proposed a wireless power transmission system (WPT) through inductive coupling and analyzed the power efficiency of the inductive coupling. The WPT included a charging station, which can provide energy through an induction coil array, and a portable energy receiving device mounted on the base of the UAV. Moreover, the power efficiency was analyzed though the equivalent circuit of WPT and the mathematical model of the power efficiency was established. The results showed that the WPT can transfer energy to UAV with high power efficiency within a 30 mm lateral displacement range.